Potential mechanisms within the digital stress-management intervention StressProffen for cancer survivors: a qualitative study post randomized controlled trial - Varsi, Cecilie; Børøsund, Elin; Ehlers, Shawna L.; Clark, Matthew M.; Andrykowski, Michael A.; Solberg Nes, Lise (Frontiers in Psychology, 2026)
BackgroundCancer diagnoses and treatment are characterized by physical and psychological stressors. Evidence-based psychosocial stress-management interventions offer physical and psychological relief, but are not always available. Results from clinical trials show the digital, evidence-based, and user-centered stress-management intervention StressProffen to be associated with reduced stress, anxiety, and depression, as well as improved self-regulatory capacity and quality of life for cancer survivors. While such interventions can be efficacious, the actual mechanisms of these effects remain understudied.ObjectiveTo qualitatively explore potential mechanisms in terms of psychological and behavioral change for cancer survivors after 12 months of access to StressProffen.MethodsUsing a selection matrix to ensure variation in sex, age, diagnosis, and program progress, the current study invited 39 participants who had access to StressProffen over 12 months through a randomized controlled trial (RCT) to participate in post-RCT semi-structured qualitative interviews related to use and potential benefit. Interview transcripts were analyzed using thematic analysis.ResultsTwenty-six cancer survivors completing the RCT agreed to participate. Qualitative analyses yielded five themes based upon patient-reported changes attributed to StressProffen use: (1) Self-awareness and personal values; who I am and what I want; (2) Comprehension; reflection and understanding of difficult thoughts and emotions; (3) Social relationships; manage my relations, (4) Relaxation and focusing skills; learn new relaxation, distraction, and focusing techniques; and (5) Coping skills and adjustment; coping with, adjusting to, and being prepared for difficult situations in all aspects of life.ConclusionAccess to digital stress-management interventions, such as StressProffen, has been shown to contribute to improved psychological wellbeing and quality of life for cancer survivors. Qualitative analyses of patient-reported benefits suggest mechanisms of enhanced self-awareness, improved comprehension of the relationship between thoughts and emotions, stronger social relationships, and improved skill self-efficacy in terms of relaxation, focusing, and coping skills. A mixed methods approach, including quantitative as well as qualitative analyses, can facilitate in-depth explorations of the impact of digital psychosocial interventions for cancer survivors.